2021
DOI: 10.1002/jsfa.11370
|View full text |Cite
|
Sign up to set email alerts
|

The effect of arbuscular mycorrhizal fungi on the phenolic compounds profile, antioxidant activity and grain yields in wheat cultivars growing under hydric stress

Abstract: BACKGROUND: Hydric stress affects the production of wheat (Triticum aestivum L.) worldwide, making some tools necessary to cope with the decrease in rainfall. A sustainable alternative is the use of arbuscular mycorrhizal fungi (AMF) as biofertilisers.Here, we analysed the effects of AMF strains adapted or non-adapted to hyper-arid conditions on the phenolic profiles and antioxidant activities of wheat grains from two cultivars with contrasting tolerance to osmotic stress (Ilustre, moderately tolerant; and Max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 62 publications
0
15
0
Order By: Relevance
“…Phenols act as a defense mechanism against herbivores, microorganisms, and competing plants [ 39 ]. In wheat plants, under AMF inoculation, the concentrations of total phenols depend on the genotype, physiological, and environmental factors, as well as the phenological stage of the crop [ 27 , 40 , 41 ]. The accumulation of phenols is very important to counteracting the negative impacts generated by drought stress in plants [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Phenols act as a defense mechanism against herbivores, microorganisms, and competing plants [ 39 ]. In wheat plants, under AMF inoculation, the concentrations of total phenols depend on the genotype, physiological, and environmental factors, as well as the phenological stage of the crop [ 27 , 40 , 41 ]. The accumulation of phenols is very important to counteracting the negative impacts generated by drought stress in plants [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Zea mays L. under AMF inoculation, there is a lower concentration of MDA than in uninoculated plants [ 49 ]. Another study with T. aestivum L. inoculated with F. mosseae under water stress produced improvements in the composition of phenols and antioxidant activities in the grains of the wheat plants, with an increase of up to 30.2% in the concentration of apigenin-C-pentoside-C-hexoside III under water stress with respect to normal irrigation [ 27 ]. Antioxidant activity is related to the purpose of protecting plants against the effects of drought stress, which generates a regulation of intracellular concentrations of ROS [ 50 ], the most common ROS are singlet oxygen, superoxide radicle, hydrogen peroxide, and hydroxyl radicle [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to these properties, mycorrhiza is considered an important and eco-friendly biofertilizer that contributes to sustainable agriculture and forestry by mitigating abiotic and biotic stress in plants [ 22 , 28 ]. One of the potential mechanisms of how arbuscular mycorrhiza fungi alleviates abiotic stress is related to their capability to increase the production of different antioxidants including phenolic compounds that counteract the oxidative stress triggered by abiotic stressors [ 29 , 30 ]. Although it is well known that condensed tannins, an important group of phenolics for oak species, are highly temperature dependent [ 31 ], it was recently reported that levels and distribution of condensed tannins vary greatly depending on the type of mycorrhiza that forms a symbiosis with a plant [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…This was beneficial for the vitality of the AMF-inoculated plants, which might be partly due to the higher proline level because proline also plays an important role in ROS detoxification. Nahuelcura et al [ 72 ] observed a significant increase in antioxidant capacity after inoculating wheat ( Triticum aestivum L.) plants with 6000 Funneliformis mosseae spores per plant while subjected to a severe six-month drought stress period. Mohammadi et al [ 73 ] in buckwheat ( Fagopyrum esculentum Moench) observed that when using a mixture (1:1:1) of mycorrhizal fungi of Rhizophagus fasciculatus , Funneliformis mosseae , and Rhizophagus irregularis at a dose of 525 spores per plant and a 2-month severe drought stress period, the total antioxidant capacity increased significantly.…”
Section: Discussionmentioning
confidence: 99%